2020
DOI: 10.1088/2053-1583/ab6d79
|View full text |Cite
|
Sign up to set email alerts
|

Hematite at its thinnest limit

Abstract: Motivated by the recent synthesis of two-dimensional α-Fe2O3 [Balan et al. Nat. Nanotech. 13, 602 (2018)], we analyze the structural, vibrational, electronic and magnetic properties of singleand few-layer α-Fe2O3 compared to bulk, by ab-initio and Monte-Carlo simulations. We reveal how monolayer α-Fe2O3 (hematene) can be distinguished from the few-layer structures, and how they all differ from bulk through observable Raman spectra. The optical spectra exhibit gradual shift of the prominent peak to higher ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The in-plane lattice parameters are found to be a = b = 5.17 Å in the most stable AFM configuration, which is slightly larger (2.5%) than that of the experimental lattice parameters of 5.04 Å 4 and in a very good agreement with the recent DFT report . The thickness of the relaxed sheet, which we refer to as a monolayer, is found to be 3.02 Å, matching very well with the previous report…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The in-plane lattice parameters are found to be a = b = 5.17 Å in the most stable AFM configuration, which is slightly larger (2.5%) than that of the experimental lattice parameters of 5.04 Å 4 and in a very good agreement with the recent DFT report . The thickness of the relaxed sheet, which we refer to as a monolayer, is found to be 3.02 Å, matching very well with the previous report…”
Section: Resultssupporting
confidence: 91%
“…In contrast to the Gaussian smearing method employed in ref. , we have used a more accurate tetrahedron method to calculate the occupancies of the states around the Fermi level, which does not depend on the smearing parameter …”
Section: Resultsmentioning
confidence: 99%
“…Recently, the effort on the synthesis of 2D structures of non-layered bulk materials has increased exponentially. With this regard, the 2D forms of Cr 2 S 3 [24], hematite [25,26], gallenene [27], and very recently ZnSb [28] have been demonstrated using different experimental techniques. Among the non-layered bulk materials, ZnSb has been extensively studied due to it promising thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…22 The 2D hematene can be easily modulated and exhibits unique properties in comparison to its bulk counterpart. 23,24 Hematene has a narrower band gap compared to hematite, and it is an antiferromagnetic ground-state semiconductor. 25−27 Previous study revealed that the curie temperature increases monotonically with the compressive strains in hematene, which broadens its applications for spintronic, memory-based devices and valleytronics.…”
mentioning
confidence: 99%
“…25 The optical and electronic properties of single-and multilayer hematene have been investigated by theoretical simulations; the prominent peak of the optical spectra shifts to higher energy, and the Morin transition temperature increases when it is reduced to a monolayer. 23 Additionally, Shang et al 24 claimed that Lidecorated hematene has a net out-of-plane magnetization on surface Fe atoms induced by the ferroelectric and ferromagnetic polarization. The hematene energetically prefers to be passivated with OH groups on the surface under oxygen-rich conditions, and its electronic structure could be tuned by mechanical deformation.…”
mentioning
confidence: 99%